2010
DOI: 10.1007/s00701-010-0702-x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin improves early functional results after experimental spinal cord injury

Abstract: This study showed the neuroprotective effects of curcumin on experimental SCI model. By increasing tissue levels of GSH-Px, SOD, and CAT, curcumin seems to reduce the effects of injury to the spinal cord, which may be beneficial for neuronal survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 45 publications
4
34
0
2
Order By: Relevance
“…Both PTEN/Akt/mTOR signaling and neuronal activity play a role in phosphorylation and, [38,39]. Relevant to this study, it is interesting to note that in distinct type of cancer cells, curcumin increased levels of phospho-eIF4e [37], which we found to be downregulated in sensorimotor neocortices after SCI.…”
Section: Discussionsupporting
confidence: 66%
“…Both PTEN/Akt/mTOR signaling and neuronal activity play a role in phosphorylation and, [38,39]. Relevant to this study, it is interesting to note that in distinct type of cancer cells, curcumin increased levels of phospho-eIF4e [37], which we found to be downregulated in sensorimotor neocortices after SCI.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, biochemical analysis of the plasma and spinal cord tissue verified its systemic and local effects. Previously, Cemil et al 6 reported the neuroprotective effects of curcumin on experimental spinal cord injury induced by aneurysmal clipping. Thereafter, Lin et al 19 performed hemisection on the spinal cord and showed curcumin reduction of robust RANTES production in reactivated astrocytes both in vitro and in vivo may contribute to its neuroprotection and potential application in spinal cord ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…29,40 Extensive research within the past decade has established curcumin as a pleotropic molecule, which is useful for neurodegenerative, cardiovascular, pulmonary, metabolic, arthritic, and autoimmune diseases. 24 Cemil et al 6 showed neuroprotective effects of curcumin in an experimental spinal cord ischemia model.…”
mentioning
confidence: 99%
“…[11] In s study conducted by Cemil et al, post-SCI effects of curcumin and MP were compared in biochemical and histopathological terms. [12] Curcumin, another polyphenol, has antioxidative, anticancerous, and anti-inflammatory effects. In curcumin group, tissue malondialdehyde (MDA) level decreased and levels of antioxidant enzymes copper-zinc superoxide dismutase, catalase, and phospholipid hydroperoxide glutathione peroxidase increased.…”
Section: Discussionmentioning
confidence: 99%